2003
DOI: 10.1002/pssb.200303527
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and electronic properties of InGaN alloys

Abstract: The In x Ga 1-x N system has electronic band gaps extending from under 1eV to 3.4 eV, and as such they are used as the active layer in commercially available visible-light emitting devices. There are many interesting features that make these nitride semiconductor alloys especially useful for efficient light emitters. It has been conjectured that the combination of piezoelectric fields and local composition inhomogeneities may be responsible for the observed high emission efficiencies, in spite of their charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
91
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(97 citation statements)
references
References 22 publications
5
91
0
1
Order By: Relevance
“…31,54 The degradationobservedwith increasing thickness is generally attributed to strain relaxation, 31,34 and/or to V-defects due to threading dislocations, 34 and/or to phase separation due to spinodal decomposition. 55 The presentwork points out that even in the absence of stress and threading dislocations, In-rich nitride alloys grown with the (0001) orientation have a strong tendency to form V-defects, which can eventually lead to phase separation.This phase separation is not due to spinodal decomposition (In 0.17 Al 0.83 N was shown to be stable up to 960°C) 56 but to a different incorporation of indium on concave or convex shape surfaces of the V-defects. …”
Section: Discussionmentioning
confidence: 69%
“…31,54 The degradationobservedwith increasing thickness is generally attributed to strain relaxation, 31,34 and/or to V-defects due to threading dislocations, 34 and/or to phase separation due to spinodal decomposition. 55 The presentwork points out that even in the absence of stress and threading dislocations, In-rich nitride alloys grown with the (0001) orientation have a strong tendency to form V-defects, which can eventually lead to phase separation.This phase separation is not due to spinodal decomposition (In 0.17 Al 0.83 N was shown to be stable up to 960°C) 56 but to a different incorporation of indium on concave or convex shape surfaces of the V-defects. …”
Section: Discussionmentioning
confidence: 69%
“…Thermodynamic calculations then showed that there is a miscibility gap in the In x Ga 1-x N system and that for typical compositions (x~0.1 for blue emission, x~0.2 for green) and typical InGaN growth temperatures (600-800 deg C) the unstrained homogeneous alloy is unstable, leading to decomposition into In-rich and In-poor regions [5]. It is not clear how applicable these equilibrium thermodynamic calculations are to the InGaN layers grown by MOVPE or Molecular Beam Epitaxy (MBE)(see later), but Ponce et al [6] have reported phase separation in MOVPE grown thick (200 nm) epilayers of InGaN with In fractions of 0.1 and above.…”
Section: Thermodynamicsmentioning
confidence: 99%
“…1,2 However, due to the immiscibility of alloy constituents, chemically induced phenomena, such as phase separation and compositional pulling, may take place, resulting in complex defect microstructures that are sensitive to the growth conditions. [3][4][5][6] The fluctuations in the indium concentration can be either long-or short-range in character. Short-range ones cause the local depletion of indium around regions that exhibit higher InN molar fraction.…”
mentioning
confidence: 99%